Linear and spatial correlation between common bean yield and porosity of a red latosol inselvíria (MS), Brazil - Megda, Marcio Mahmoud [UNESP]; De Passos e Carvalho, Morel [UNESP]; Vieira, Michele Xavier [UNESP]; Andreotti, Marcelo [UNESP]; Pereira, Elaine Cristina [UNESP] (FapUNIFESP (SciELO), 2008)
Soil porosity influences plant development since root growth and crop yield are determined by the root depth. The objective of this study was to investigate the linear and spatial variability and correlations between common bean yield and soil porosity. The bean grain yield of the irrigated cultivar Carioca IAC was analyzed in the growing season 2004/2005, in Selviria-MS, as well as macroporosity (MA), microporosity (MI) and total porosity (TP), in a Dystroferric Red Latosol, at four depths: 1 (0.0-0.10 m), 2 (0.10-0.20 m), 3 (0.20-0.30 m) and 4 (0.30-0.40 m). Soil and plant data were collected in a geostatistical grid with 135 points spaced 10 m apart, covering an area of 50 × 150 m. The data of the studied attributes did not vary randomly and the values were intermediate to low. They followed well-defined spatial standards, reaching between 11.70-104.40 m. On the other hand, the linear correlation between the plant and soil attributes was low, due to the high number of observations. Grain yield had the best linear correlations with MA1b, Mil and TP3. From the spatial point of view, the inverse correlation between PG and #TP2 was outstanding. At the sites where #TP2 diminished (0.030-0.045 m3 m-3) the yield varied from 2,173 to 3,529 kg ha-1 and where it increased (0.045-0.076 m3 m-3), the yield was between 1,630 and 2,173 kg ha-1. Therefore, the total soil porosity, evaluatedin the 0.10-0.20 m layer (#TP2), indicated the importance of the contact root/soil and was in turn a satisfactory indicator of soil physical quality, with a view to the grain yield of irrigated common bean.
Correlação linear e espacial entre a produtividade de feijão e a porosidade de um latossolo vermelho de selvíria (MS)
Keywords: No-tillage; Phaseolus vulgaris L.; Soil management; Spatial variability